Viloxazine in the Treatment of Attention Deficit Hyperactivity Disorder - Edinoff, Amber N.; Akuly, Haseeb A.; Wagner, John H.; Boudreaux, Megan A.; Kaplan, Leah A.; Yusuf, Shadman; Neuchat, Elisa E.; Cornett, Elyse M.; Boyer, Andrea G.; Kaye, Adam M.; Kaye, Alan D. (Frontiers in Psychiatry, 2021)
Attention deficit hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder in children. Over the past twenty years, research on the disease and its characteristics and treatment options has grown exponentially. The first-line pharmacologic treatment of ADHD is stimulants, which have a response rate of ~70%. With the support of four phase 3 studies involving more than 1,000 pediatric patients 6–17 years old, the FDA has approved the non-stimulant, serotonin-norepinephrine modulating agent (SNMA) viloxazine in an extended-release capsule (viloxazine ER) for treatment of ADHD in children aged 6–17. Viloxazine modulates serotonergic activity as a selective 5-HT22B receptor antagonist and 5-HT2C receptor agonist and moderately inhibits norepinephrine transporter (NET), thus blocking the reuptake of norepinephrine. A phase 2 study by Johnson et al. found that once-daily dosing of viloxazine ER in 200, 300, or 400 mg dosages in children with ADHD for eight weeks resulted in a statistically significant reduction of ADHD-RS-IV total score. A post hoc analysis of data from four phase 3, randomized, placebo-controlled, double-blind, three-arm, clinical trials by Faraone et al. found that early response to viloxazine treatment, defined as a change in ADHD-RS-5 total score at week 2, best predicted the treatment response at week 6 [75% positive predictive power (PPP), 75% sensitivity]. Proper treatment of the symptoms and comorbidities associated with ADHD is crucial in improving a patient's quality of life, cognitive function, and overall therapeutic outcomes. Viloxazine's mechanism of action, clinical effects, and limited side effect profile point toward the drug's relevance in the treatment of ADHD.